2021
DOI: 10.1021/acs.jpca.1c09150
|View full text |Cite
|
Sign up to set email alerts
|

Large Inverted Singlet–Triplet Energy Gaps Are Not Always Favorable for Triplet Harvesting: Vibronic Coupling Drives the (Reverse) Intersystem Crossing in Heptazine Derivatives

Abstract: Heptazine derivatives are promising dopants for electroluminescent devices. Recent studies raised the question whether heptazines exhibit a small regular or an inverted singlet–triplet (IST) gap. It was argued that the S1 ← T1 reverse intersystem crossing (RISC) is a downhill process in IST emitters and therefore does not require thermal activation, thus enabling efficient harvesting of triplet excitons. Rate constants were not determined in these studies. Modeling the excited-state properties of heptazine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 43 publications
(96 reference statements)
0
50
0
Order By: Relevance
“…However, increasing the active space to 14 electrons in 14 orbitals (14,14) yielded an inverted singlet-triplet gap for all six molecules. Considering the dynamic correlation at the CASPT2 level on top of the (12,9) CASSCF calculations also led to the exhibition of the INVEST property in all the studied molecules. CASPT2 calculation with a (14,14) reference on molecule 1 yielded almost the same singlet-triplet gap as obtained in the (12,9) CASPT2 calculation suggesting that the energy gaps obtained in the CASPT2 (9,12) calculations are accurate.…”
Section: Ab Initio Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, increasing the active space to 14 electrons in 14 orbitals (14,14) yielded an inverted singlet-triplet gap for all six molecules. Considering the dynamic correlation at the CASPT2 level on top of the (12,9) CASSCF calculations also led to the exhibition of the INVEST property in all the studied molecules. CASPT2 calculation with a (14,14) reference on molecule 1 yielded almost the same singlet-triplet gap as obtained in the (12,9) CASPT2 calculation suggesting that the energy gaps obtained in the CASPT2 (9,12) calculations are accurate.…”
Section: Ab Initio Methodsmentioning
confidence: 83%
“…Calculations at the CASSCF level using an active space with 12 electrons in 9 orbitals (12,9) showed that molecules 1, 2, and 3 are INVEST molecules, whereas 4, 5, and 6 are not. However, increasing the active space to 14 electrons in 14 orbitals (14,14) yielded an inverted singlet-triplet gap for all six molecules.…”
Section: Ab Initio Methodsmentioning
confidence: 99%
“…The RISC rate from T 2 to S 1 computed without accounting for vibronic effects (HT-like or reverse internal conversion from T 1 to T n ) leads to a range of values compatible with that measured experimentally for MR-TADF emitters (see Table 3). However, recently, Marian et al 62 highlighted the critical role played by the Herzberg–Teller mechanism in promoting a non-vanishing SOC for mediating an efficient S 1 –T 1 interconversion in heptazine and its derivative, leading to an increase in RISC rate resulting from symmetry lowering. Furthermore, a similar mechanism is also expected to enhance the S 1 –T n spin interconversion.…”
Section: Rate Constants Calculationmentioning
confidence: 99%
“… 14 Dinkelbach et al studied the effect of negative singlet–triplet gap and vibronic coupling in heptazine derivatives using the DFT/multireference configuration interaction (DFT/MRCI) approach. 23 Sancho-Garcia and co-workers suggested that small chemical modifications of the triangle derivatives can produce good candidates for inverted singlet–triplet gap using several single reference correlated methods like spin-component scaled second-order coupled cluster (SCS-CC2), 24 second-order ADC [ADC(2)], 25 and multireference methods like complete active space self-consistent field (CASSCF) and N-electron valence second-order perturbation theory (NEVPT2). 26 28 Domain-based local pair natural orbital (DLPNO) similarity transformed EOM-CCSD (STEOM-CCSD) 29 have accurately predicated inverted singlet–triplet gaps as well.…”
Section: Introductionmentioning
confidence: 99%